Monetary Operations and Government Debt Management Under Islamic Banking. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper outlines the recent progress in developing Islamic financial instruments for the management of monetary policy and public borrowing requirements and provides details on new instruments currently being developed in the Islamic Republic of Iran and Sudan. The paper also touches on the institutional arrangements for interbank market operations and the design of effective central bank credit facilities that are needed under Islamic banking to support the development and operation of these new instruments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet